Optimalisasi Pendidikan Agama Islam dalam Membina Generasi Qur’ani Melalui Kegiatan Mengaji Rutin Anak-Anak di Desa Bangun Sari - Aprillia, Widya; Mavianti, Mavianti (Cendekia : Jurnal Pendidikan dan Keagamaan, 2025)
This study describes the implementation and impact of regular Quran recitation activities for children in optimizing Islamic Religious Education (PAI) to foster a Qur'anic generation in Bangun Sari Village, Setia Janji District, Asahan Regency. The activity was carried out through the Thematic Community Service Program of the University of Muhammadiyah North Sumatra in September 2025, involving children, parents, community leaders, and students. This study applied a descriptive qualitative method, where information was collected through observation, interviews, and document searches. All information was then processed narratively to describe the process and findings that emerged. The results showed that the recitation activities went well and received community support. The program focused on tahsin, tahfidz, and the formation of religious character traits such as discipline and responsibility. Approximately 75% of participants experienced an improvement in their ability to read the Qur'an and memorize short surahs. In addition to strengthening religious values, this activity also fostered a spirit of community among the community, and for students, this program became a valuable experience in applying their knowledge and fostering social empathy.